The Application of Inorganic Nanoparticles in Molecular Targeted Cancer Therapy: EGFR Targeting - Sun, Meng; Wang, Ting; Li, Leijiao; Li, Xiangyang; Zhai, Yutong; Zhang, Jiantao; Li, Wenliang (Frontiers in Pharmacology, 2021)
Epidermal growth factor receptor (EGFR) is found to be one anticancer drug target for a number of cancers, such as nonsmall cell lung cancer and so on. However, unsatisfying treatment effect, terrible side-effects and development of drug resistance are remaining insurmountable challenges of EGFR targeting treatments for cancers. With the advancement of nanotechnology, an increasing number of inorganic nanomaterials are applied in EGFR-mediated therapy to improve those limitations and further potentiate the efficacy of molecular targeted cancer therapy. Given their facile preparation, easy modification and biosecurity, inorganic nanoparticles (iNPs) have been extensively explored in cancer treatments to date. This review presents an overview of various iNPs targeting EGF and their applications in tumor therapy. Moreover, we also highlight future perspectives regarding their remaining issues. We hope these discussions could inspire future research on EGFR-targeted iNPs.